Sleep related breathing disorders - Nangia, Vivek; Swami, Shivani (Jaypee, the health sciences publisher, 2015)
Comprehensive guide to sleep related breathing disorders with a focus on snoring and sleep apnoea. Includes both surgical and non-surgical management.